The Doomsday argument and the self-indication assumption: reply to Olum - Bostrom, N; Ćirković, M (Blackwell Publishing, 2003)
In a recent paper in this journal, Ken Olum attempts to refute the Doomsday argument by appealing to the self-indication assumption (SIA), the idea that your very existence gives you reason to think that there are many observers. In contrast to earlier refutation attempts that use this strategy, Olum confronts and try to counter some of the objections that have been made against SIA. We argue that his defense of SIA is unsuccessful. This does not, however, mean that one has to accept the Doomsday argument (or the other counterintuitive results that flow from related thought experiments). A developed theory of observation selection effects shows why the Doomsday argument is inconclusive and how one can consistently reject both it and SIA.